Hubungan Keaktifan Pelayanan Gereja dengan Kesehatan Mental Pemuda Kristen - Merfin Bengkiuk; Boas Tauho; Junias Selan; Sandriana Ludji; Yusmin Tapeun; Adriana Sole (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2026)
The mental health of Christian youth has become an important issue because various life demands can affect their psychological well-being. Church ministry is often regarded as a means of supporting the spiritual, social, and emotional development of young people. This study aims to examine the level of church ministry involvement, the mental health condition of Christian youth, and the relationship between the two variables. The study employed a quantitative method with a descriptive correlational approach involving 30 Christian youth participants. Data were collected through questionnaires and analyzed using descriptive statistics, linearity testing, and simple linear regression. The findings indicate that the level of church ministry involvement was relatively high, while the respondents’ mental health was generally in a good category. Regression analysis produced a correlation coefficient of 0.278 with a significance value of 0.137, indicating that the relationship between the two variables was positive but not statistically significant. The study concludes that active involvement in church ministry is not a primary factor determining the mental health of Christian youth. The novelty of this study lies in the finding that church ministry functions as a supporting factor rather than a primary determinant of mental health, highlighting the need for a more holistic ministry approach to promote the well-being of Christian youth.